ISLAMIC EDUCATION-BASED MANAGEMENT OF ELEMENTARY SCHOOLS IN DEVELOPING RELIGIOUS MODERATION - Karwadi, Karwadi; Fitria, zahratul; Indrawan, Deni (Pusat Penerbitan Universitas (P2U) Unisba, 2023)
Primary school Islamic education institutions that organize teaching and learning activities must be involved in developing human resources and improving quality in Indonesia. To achieve this goal, primary school Islamic education institutions must be managed optimally. This research is a library study (library search) which requires researchers to be able to understand the subject matter under study, especially references to various relevant empirical phenomena. The result of this research is the implementation of the management of Islamic educational institutions by applying the functions of Islamic education administration (planning, organizing, directing, and supervising) comprehensively and consistently by internalizing the values of religious moderation as a smart and advanced education seeking strategy